“Eu nem sabia que era negra até te conhecer”: literatura com temática da cultura africana e afro-brasileira para crianças pequenas da educação infantil - Santos, Rosângela Pereira dos (2023)
The central theme of this dissertation is the investigation of the manifestations of black children in early childhood education about their ethnic-racial belongings, when they interact with literature with themes of African and Afro-Brazilian culture. The question that motivated the study was: do moments of contact with works of children's literature with themes of African and Afro-Brazilian culture enable dialogues and reflections that contribute to strengthening the identities of black children? The general objective was to analyze the manifestations (speech, gestures, emotions, image representations) of black children between four and five years of age in an early childhood education class about their ethnic-racial belongings, when in contact with literature on cultural themes. African and Afro-Brazilian. Arising from this, the specific objectives were: to observe how young children interact with literary books that focus on African and Afro-Brazilian culture; investigate aspects of children's identity, self-image, relationship between child/teacher and child/child, based on ethnic-racial belonging; identify the influence of positive representations of black characters in children's literature on the ethnic-racial belonging of black children; prepare, as an educational product, a report of postgraduate experiences. To this end, the methodology that conducted this investigation was through action research, from the perspective of Michel Thiollent (2000), with a qualitative approach. Structured around the themes of literature, childhood, identity and ethnic-racial relations, the theoretical framework that supported this study is composed by Eliane Debus (2017), Débora Cristina de Araujo (2018), supporting the discussions on literature; Eliane Cavalleiro (2020), Caroline F. Jango (2017), Anete Abramowicz and Fabiana de Oliveira (2012), Fúlvia Rosemberg (2011), Lucimar Rosa Dias (2007), Sara da Silva Pereira (2019), with an approach to childhood and ethnic-racial relations; Nilma Lino Gomes (2017), Kabengele Munanga (2005), with discussions on race and identity. The results from the research indicate that if, on the one hand, black children in early childhood education demonstrate fear regarding the judgment of white children regarding their ethnic-racial belonging, on the other hand, literature on the themes of African and Afro-Brazilian culture has influenced the way in which Many build their ethnic-racial identity, and it is possible to see that after contact with books, there were changes in the racial self-declaration of some black children. In addition to providing an experience with literature and a stimulus for reader training, books that contain in their plots characters that come close to the racial reality of children in a leading role in a humanized way and experiencing everyday activities, as well as receiving affection and appreciation as due to their blackness, they enable a positive racial construction for black children. For white women, they also provide education from an anti-racist perspective which, from early childhood education, can mobilize the appreciation of other human experiences. The importance of Ethnic-Racial Relations Education in the initial and continuing training of teachers is also a finding that has already been highlighted in other studies and reaffirmed by this research.